Complex problem analysis of the Hungarian milk product chain - Blaskó, Beáta (Acta Agraria Debreceniensis, 2011)
Hungarian dairy sector went through significant changes in past two decades. The most significant changes were caused by our accession to the European Union. In Hungary milk production remarkably declined after EU accession. The size of our dairy herd has been practically reducing since the political transformation, but increasing yields per cow could compensate it in some way and for some time. However, in recent years, increasing yield per cow came to a stop and in parallel, the number of cows declined further and faster. Low prices, high production costs and tightening quality requirements ousted several producers from the market in past years. Feeding cost represents the highest rate in cost structure of production, but animal health expenditures and various losses are also significant. There are undeniably competitive disadvantages in the level of organisation and labour productivity; however competitiveness already depends on cost effectiveness in the medium run. In Hungary concentration of the dairies is relatively strong in spite of the relative high number of corporations. The dairies compete with each other and with the export market for the raw material and the better exploitation of their capacities. Applied technology of the Hungarian dairies lags behind the Western-European competitors’; in addition they have handicaps in efficiency and product innovation. Presence of chain of stores being dominant in sale of milk products does also not favour in all respects to the position of the dairies. The aforementioned retail chains are namely consumer-centric, engage in price follower conduct and weaken the position of the dairies with their private label products. As a result of increasing import of milk and milk products Hungary became a net importer in recent years. Today, disposable income still essentially determines the consumption habits of price-sensitive consumers. Loyalty for Hungarian products is not typical, consumers are open for import products being preferred by retail chains. In addition Hungarian milk and milk product consumption is about half of the Union average and it is far behind the level being necessary for healthy eating. In Hungary lack of competitiveness and vertical integration relationships and backwardness are revealing among the dairy farmers and the dairies, while chain of stores are in unprecedented “monopolistic situation”; the whole sector can be characterised by defencelessness.